Unveiling the Membrane and Cell Wall Action of Antimicrobial Cyclic Lipopeptides: Modulation of the Spectrum of Activity - Roser Segovia; Judith Solé; Ana Maria Marqués; Yolanda Cajal; Francesc Rabanal (MDPI AG, 2021)
Antibiotic resistance is a major public health challenge, and Gram-negative multidrug-resistant bacteria are particularly dangerous. The threat of running out of active molecules is accelerated by the extensive use of antibiotics in the context of the COVID-19 pandemic, and new antibiotics are urgently needed. Colistin and polymyxin B are natural antibiotics considered as last resort drugs for multi-resistant infections, but their use is limited because of neuro- and nephrotoxicity. We previously reported a series of synthetic analogues inspired in natural polymyxins with a flexible scaffold that allows multiple modifications to improve activity and reduce toxicity. In this work, we focus on modifications in the hydrophobic domains, describing analogues that broaden or narrow the spectrum of activity including both Gram-positive and Gram-negative bacteria, with MICs in the low µM range and low hemolytic activity. Using biophysical methods, we explore the interaction of the new molecules with model membranes that mimic the bacterial inner and outer membranes, finding a selective effect on anionic membranes and a mechanism of action based on the alteration of membrane function. Transmission electron microscopy observation confirms that polymyxin analogues kill microbial cells primarily by damaging membrane integrity. Redistribution of the hydrophobicity within the polymyxin molecule seems a plausible approach for the design and development of safer and more selective antibiotics.